2021
DOI: 10.3390/plants10071443
|View full text |Cite
|
Sign up to set email alerts
|

Growth Promotion or Osmotic Stress Response: How SNF1-Related Protein Kinase 2 (SnRK2) Kinases Are Activated and Manage Intracellular Signaling in Plants

Abstract: Reversible phosphorylation is a major mechanism for regulating protein function and controls a wide range of cellular functions including responses to external stimuli. The plant-specific SNF1-related protein kinase 2s (SnRK2s) function as central regulators of plant growth and development, as well as tolerance to multiple abiotic stresses. Although the activity of SnRK2s is tightly regulated in a phytohormone abscisic acid (ABA)-dependent manner, recent investigations have revealed that SnRK2s can be activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 139 publications
(275 reference statements)
0
14
0
Order By: Relevance
“… 24 , 25 In angiosperms, SnRK2s are a key component of ABA signaling pathways mediated by ABA receptors (PYR/PYL/RCAR) and protein phosphatase 2Cs (PP2CAs), and are also divided into three subclasses: I, II, III based on amino acid sequence similarity and ABA response. 26 , 27 However only D-rich SnRK2s (subclass II and III) are activated by ABA, osmotic stress activates all SnRK2 members except Arabidopsis SRK2J/SnRK2.9 (subclass I). As a result, SnRK2s from subclass II and III are categorized as ABA-responsive SnRK2s, whereas SnRK2s from subclass I are classified as ABA-unresponsive SnRK2s.…”
Section: Snrk2 Kinases In the Earliest Land Plantsmentioning
confidence: 99%
“… 24 , 25 In angiosperms, SnRK2s are a key component of ABA signaling pathways mediated by ABA receptors (PYR/PYL/RCAR) and protein phosphatase 2Cs (PP2CAs), and are also divided into three subclasses: I, II, III based on amino acid sequence similarity and ABA response. 26 , 27 However only D-rich SnRK2s (subclass II and III) are activated by ABA, osmotic stress activates all SnRK2 members except Arabidopsis SRK2J/SnRK2.9 (subclass I). As a result, SnRK2s from subclass II and III are categorized as ABA-responsive SnRK2s, whereas SnRK2s from subclass I are classified as ABA-unresponsive SnRK2s.…”
Section: Snrk2 Kinases In the Earliest Land Plantsmentioning
confidence: 99%
“…The ABA-activated MAPK cascade, in which MAP 3Ks/MAP 3 K17/MAP 3 K18 activate MKK3 and then stimulate the activity of MPK1/MPK2/MPK7/MPK14, plays an important role in the stress response [ 52 ]. SnRK2-mediated signaling is also involved in maintaining osmotic homeostasis, contributing to plant growth [ 49 , 53 ]. A previous study showed that SnRK2.8 functions as a regulatory factor in the stress response and that overexpression of SnRK2.8 enhances stress tolerance in Arabidopsis [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that ABA is a key phytohormone in the responses of plants to osmotic stress, the main ABA signaling pathway, referred to as the PYR/PYL/RCAR‐PP2Cs‐SnRK2s cascade, has been extensively studied (Fujita et al., 2011). In the osmotic stress response, subclass III SnRK2 (2.2/2.3/2.6) protein kinases function as positive modulators of ABA, which transfer the ABA signaling to downstream target proteins (Kamiyama et al., 2021). Activated SnRK2.6 phosphorylates these downstream targets, which include transcription factors, anion channels, and enzymes, and the induced cellular processes in turn trigger ABA‐mediated responses, including inhibition of seed germination, plant growth, and stomatal opening (Cutler et al., 2010; Kamiyama et al., 2021; Sah et al., 2016; Soma et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the osmotic stress response, subclass III SnRK2 (2.2/2.3/2.6) protein kinases function as positive modulators of ABA, which transfer the ABA signaling to downstream target proteins (Kamiyama et al., 2021). Activated SnRK2.6 phosphorylates these downstream targets, which include transcription factors, anion channels, and enzymes, and the induced cellular processes in turn trigger ABA‐mediated responses, including inhibition of seed germination, plant growth, and stomatal opening (Cutler et al., 2010; Kamiyama et al., 2021; Sah et al., 2016; Soma et al., 2021). However, although SnRK2.6 is among the core components implicated in osmotic stress responses, the range of proteins targeted by this kinase has yet to be fully characterized.…”
Section: Introductionmentioning
confidence: 99%